Three types of pulsed signal trains emitted by Indo-Pacific humpback dolphins (Sousa chinensis) in Beibu Gulf, South China Sea - Wang, Xiao-yan; Jiang, Ying; Liu, Zong-wei; Yang, Chun-mei; Chen, Bing-yao; Lü, Lian-gang (Frontiers in Marine Science, 2022)
Pulsed signal trains comprising clicks, buzzes, and burst-pulses play important roles in the life activities of odontocetes, but they have not been distinguished in Indo-Pacific humpback dolphins. Underwater vocalizations of this species were recorded from September 27 to October 2, 2019 in the Beibu Gulf, South China Sea. Pulsed signal trains were detected with variations in the pulsed signal number (range of 6–76), mean inter-pulse interval (IPIs_m: 0.1–315 ms), and mean duration (D ranged from tens to thousands of milliseconds). Principal component analysis and hierarchical cluster analysis based on six acoustic parameters in the pulsed signal trains identified three categories of trains designated as clicks, burst-pulses, and buzzes. Buzzes and burst-pulses (different from those described in previous research) were detected for the first time in Indo-Pacific humpback dolphins in China. The results indicated that the IPIs_m was longest for clicks but shortest for buzzes, and the D values were longer for both clicks and burst-pulses than buzzes. The three train types could be identified based on the IPIs_m, with threshold values of 4.9 and 15.5 ms. The significant variations in the three vocalization types were related to surface behaviors, and buzzes could have a special function in foraging by this species, thereby requiring further research. These findings may facilitate future quantitative evaluations of the echolocation performance in wild Indo-Pacific humpback dolphins, and provide important guidance regarding acoustic observations and the identification of this species.